Seed technology in emergence and biomectric variables of the Silk Flower (Calotropis procera) (Research, Society and Development, 2021)
The silk flower (Calotropis procera) is an invasive species known as tolerant to adverse environment, native to Africa and southwestern Asia and popularized in Brazil as Jealousy, Old Bag, Kapok Flower and Silk. Highlighted by the use as forage, medicinal and even in the textile industry still requires studies that allow commercial cultivation. This work aimed to evaluate the effects of drying and rehydration of seed emergence and initial growth, in a study conducted between September and October 2018. The experimental design was a randomized block design with 04 replications and treatments consisted of 2 x 5 factorial arrangement, the first factor being the condition of the seed at planting (freshly picked or dried for 48 hours) and the second hydration (00, 02, 04, 06 e 08 hours). In each situation determinations were performed gain and loss of moisture. Fresh seeds have moisture content of around 70% and around 35% dehydrated. When rehydrated, still occurs in both cases, moisture gain respectively 18.13 and 43.33%. Rehydration improves the vigor of fresh seeds not influencing the dehydrated and not interfering with emergency total reaches 90%. Drying does not affect the depth of the root, but dramatically reduces the time, fresh weight of shoot and root between 27 and 210%.